Impact of the pulling rate on the redox state and magnetic domains of Fe-Si-O glass ceramic processed by LFZ method. (November 2020) - Salehizadeh, S.A.; Ferreira, N.M.; Ivanov, M.S.; Khomchenko, V.A.; Paixão, J.A.; Costa, F.M.; Valente, M.A.; Graça, M.P.F.
Graphical abstract: Highlights: The Fe-Si-O glass-ceramics were prepared by Laser Floating Zone (LFZ) technique. The influence of pulling rate variation on the crystallization kinetics and the redox state is investigated. Faster growth favors the formation of Fe-containing clusters with a higher Fe2+/Fetotal ratio. VSM measurement and AFM/MFM analysis´s results supported the findings obtained from Raman's study. Abstract: This work studies the effect of the pulling rate, varying from 100 to 400 mm/h, on the redox state, structure and magnetic properties of iron oxide bearing silica glasses processed by laser floating zone (LFZ) method. XRD analysis revealed that the maximum crystallinity is obtained in the fibre grown at the lowest pulling rate. A detailed Raman analysis demonstrated that the global content of Fe 2+ increases with pulling rate, while the growth under a lower pulling rate promotes the α-Fe2 O3 crystallization. Atomic/magnetic force microscopy provided further evidence of phase-separated iron oxide crystallites formation with a high Fe 2+ /Ftotal ratio as the pulling rate increases. The magnetic measurements performed over a wide temperature range showed that the highest magnetization is found in the fibre grown at the highest pulling rate. A strong correlation between structural-topographical features and the magnetic characteristics of the glass fibres is substantiated.